Sharia-Based Cooperatives And Systems Distribution Of Sharia Cooperatives - Rizky Amaliyah Ramdhani Ilham; Muhammad Rustam Saputra; Amiruddin.K; Mukhtar Lutfi (Wasīlah: Journal Of Sharia Sciences, 2025)
This research aims to describe sharia cooperatives are business entities that conduct economic activities based on Islamic principles, as stipulated in the Quran and Sunnah. Based on the principles of family and mutual cooperation, these cooperatives aim to improve the welfare of their members and the community at large. Principles such as being free from interest, social justice, and partnership are the hallmarks of Sharia cooperatives compared to conventional cooperatives. As a form of partnership, these cooperatives prioritize halal and sharia-compliant businesses to support fair and sustainable economic management. The principles of family and mutual cooperation are the main foundations of Sharia cooperatives, reflecting the spirit of cooperation and collective responsibility. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study show that the principles of Islamic cooperatives include the belief that wealth is a trust from Allah and not owned absolutely. Freedom of transactions, social justice, and the rejection of usury are the main foundations. The concept of deliberation replaces formal democracy in decision-making, creating harmony and togetherness among members. With a profit-sharing system instead of interest, Islamic cooperatives offer a fairer financial alternative, in accordance with Islamic teachings.